Negative chronotropic and inotropic effects of lubiprostone on iPS cell-derived cardiomyocytes via activation of CFTR - Hiraku Akita; Susumu Yoshie; Takafumi Ishida; Yasuchika Takeishi; Akihiro Hazama (BMC, 2020)
Abstract Background Lubiprostone (LBP) is a novel chloride channel opener that has been reported to activate chloride channel protein 2 (ClC-2) and cystic fibrosis transmembrane conductance regulator (CFTR). LBP facilitates fluid secretion by activating CFTR in the intestine and is used as a drug for treating chronic constipation. While ClC-2 and CFTR expression has been confirmed in cardiomyocytes (CMs), the effect of LBP on CMs has not yet been investigated. Thus, the present study aimed to investigate the effect of LBP on CMs using mouse-induced pluripotent stem (iPS) cell-derived CMs (iPS-CMs). Methods We induced mouse iPS cells into CMs through embryoid body (EB) formation. We compared the differentiated cells to CMs isolated from adult and fetal mice using gene expression, spontaneous beating rate, and contraction ratio analyses. Results Gene expression analysis revealed that, in the iPS-CMs, the mRNA expression of the undifferentiated cell markers Rex1 and Nanog decreased, whereas the expression of the unique cardiomyocyte markers cardiac troponin I (cTnI) and cardiac troponin T (cTNT), increased. Immunostaining showed that the localization of cTnI and connexin-43 in the iPS-CMs was similar to that in the primary fetal CMs (FCMs) and adult CMs (ACMs). LBP decreased the spontaneous beating rate of the iPS-CMs and FCMs, and decreased the contraction ratio of the iPS-CMs and ACMs. The reduction in the beating rate and contraction ratio caused by LBP was inhibited by glycine hydrazide (GlyH), which is a CFTR inhibitor. Conclusion These results suggest that LBP stimulates CFTR in CMs and that LBP has negative chronotropic and inotropic effects on CMs. LBP may be useful for treating cardiac diseases such as heart failure, ischemia, and arrhythmia.